Mind full or mindful: a report on mindfulness and psychological health in healthy adolescents. Issue 1 (2nd January 2016) - Tan, Lucy B.G.; Martin, Graham
Abstract : Mindfulness is defined as a non-judgemental awareness and accepting of present-moment experience. With intentional attendance to one's ongoing stream of thoughts, sensations and emotions as they arise, it allows the individual to react with less impulsivity and flexibility. However, empirical findings of mindfulness to date have largely been confined to outcome studies using clinical populations. This cross-sectional study examined the relationships between mindfulness, self-esteem, resiliency and mental health symptoms (anxiety, stress, depression and cognitive inflexibility) in a sample of 106 healthy adolescents. Participants completed a set of questionnaires. First, we found moderate effect size for anxiety, depression and self-esteem and large effect size for cognitive inflexibility. These results, when compared with clinical samples, demonstrated similar trends found in a healthy adolescent sample. Second, predictive value of mindfulness was examined and we found significant contribution of mindfulness to mental and psychological health.